2008
DOI: 10.1002/mrd.20858
|View full text |Cite
|
Sign up to set email alerts
|

A mesenchymal perspective of müllerian duct differentiation and regression in Amhr2‐lacZ mice

Abstract: The Müllerian ducts give rise to the female reproductive tract, including the Fallopian tubes, uterus, cervix, and anterior vagina. In male embryos, the Müllerian ducts regress, preventing the formation of female organs. We introduced the bacterial lacZ gene, encoding beta-galactosidase (beta-gal), into the AMHR-II locus (Amhr2) by gene targeting in mouse embryonic stem (ES) cells to mark Müllerian duct differentiation and regression. We show that Amhr2-lacZ heterozygotes express beta-gal activity in an Amhr2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
143
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(166 citation statements)
references
References 54 publications
18
143
1
Order By: Relevance
“…However, Cre-mediated excision of exon 3 from the floxed allele of β-catenin is likely to occur later, perhaps after MD regression has already started. Expression from the AMHR2 locus begins at E13 (35), and our preliminary results show that the recombined Ctnnb1 Δ(ex3) allele is only detected at E13.5 (Fig. S5B).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, Cre-mediated excision of exon 3 from the floxed allele of β-catenin is likely to occur later, perhaps after MD regression has already started. Expression from the AMHR2 locus begins at E13 (35), and our preliminary results show that the recombined Ctnnb1 Δ(ex3) allele is only detected at E13.5 (Fig. S5B).…”
Section: Discussionmentioning
confidence: 69%
“…This led us to speculate that the focal MD retention in mutant mice could result from delayed expression of CA β-catenin. Amhr2-Cre is expressed from a knockin mutation of the Amhr2 locus and its expression occurs only when the endogenous AMHR2 is expressed (4,35). However, Cre-mediated excision of exon 3 from the floxed allele of β-catenin is likely to occur later, perhaps after MD regression has already started.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with the Amhr2-LacZ reporter mouse model showed that this promoter is active for a brief period from embryonic day 12.5 to 15.5 in mesenchymal cells surrounding the Müllerian ducts (Arango et al, 2008;Jamin et al, 2002;Klattig et al, 2007). Notably, in a related reporter model, Amhr2Cre-driven recombination of a Rosa26 reporter (R26R) resulted in β-galactosidase staining of myometrial cells but not in endometrial stromal cells (Arango et al, 2008;Deutscher and Hung-Chang Yao, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Amhr2-LacZ animals (Arango et al, 2008;Arango et al, 1999) and Amhr2Cre animals (Jamin et al, 2002) were obtained from Dr RR…”
Section: Animals and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation